Atividade antifúngica, controle da pinta preta e ativação de mecanismos de defesa em tomateiro por óleos essenciais - Hendges, Camila (2019)
The early blight, caused by the fungus Alternaria solani, is one of the diseases that most affects the tomato crops, whose damage directly affects the productivity. A source of inhibition of this and other diseases is the use of essential oils, which may replace the use of fungicides, causing no harm to the environment or human. This work was carried out with the aim of evaluating the antifungal activity, the control of the early blight and activation of defense enzymes in tomato treated with the essential oils of bergamot orange (Citrus aurantium), citronella (Cymbopogon nardus) and tea tree (Melaleuca alternifolia). Experiments with each oil were conducted separately. Mycelial disks of the A. solani pathogen were deposited on Petri dishes containing the treatments: 0, 500, 1000, 1500, 2000 and 2500 μL L-1 of essential oil and fungicide (azoxystrobin + diphenoconazole), maintained in BOD at 25 °C and dark, and the parameters of mycelial growth and sporulation were evaluated. Tomato seeds were sown in an expanded polystyrene tray and after 30 days were transplanted to the ground under greenhouse conditions. After 15 days the treatments mentioned above were applied to the second pair of leaves in the lower part of the plant, and after 72 hours the pathogen was inoculated in the treated leaves (second pair of leaves) and untreated (third leaves). The severity of the disease was expressed through the area under the disease progress curve (AUDPC). The enzymes involved in the defense process were also evaluated, such as peroxidase, polyphenoloxidase and phenylalanine ammonia-lyase, using the oil concentrations of 2500 μL L-1 for bergamot, 2000 μL L-1 for citronella and 1500 μL L-1 to tea tree. The increase of the concentrations of all the essential oils decreased the mycelial growth of the pathogen. The sporulation of the pathogen decreased with the increase of the essential oil concentrations of bergamot and citronella, but to the oil of tea tree, the sporulation was favored with the addition of the concentrations. The concentration of 2500 μL L-1 resulted in the lowest AUDPC, both in treated (21.59%) and untreated (53.69%) leaves for bergamot essential oil. For citronella oil, AUDPC was reduced by 38.14% in treated leaves and 51.32% in those not treated with the concentrations of 2500 μL L-1. In the leaves treated with essential oil of tea tree, the concentration 1500 μL L-1 presented the largest reduction of AUDPC, corresponding to 53.32%, and in the untreated leaves the most effective concentration was 2000 μL L-1 with inhibition of 42.30%. Increase in the activity of peroxidase and phenylalanine ammonia-lyase was observed with the essential oils of bergamot, citronella and tea tree. The polyphenoloxidase activity, on the other hand, presented increase just with the oils of bergamot and citronella. The essential oils of bergamot, citronella and tea tree can be an alternative in the control of the early blight of tomato.